Konsep Dasar Analogi Sains Dengan Ayat-Ayat Al Qur’an Dalam Ilmu Penegetahuan - Kholik, Abd; budi, Irwan setia (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to create educational materials using a fundamental approach that correlates science with verses from the Quran (SSQ). Employing a literature review and an analytical method as part of a conceptual qualitative study, the research explores the multifaceted relationship between science and the Quran. Beyond being a sacred guide for worship and morality, the Quran is found to contain verses addressing natural phenomena and scientific concepts. The research underscores the significance of comprehending the integration of science within Quranic verses. By recognizing the Quran as a guide, it becomes apparent that the scientific knowledge in our world is intricately linked to the teachings of the Quran. This research advocates for a deeper understanding of the harmonious coexistence of science and the Quran, emphasizing the importance of recognizing the Quran as a source that enriches our comprehension of the scientific realities in our world